The Implementation of Arabic Language Learning Using Oxford Strategy in Primary School/ تنفيذ إستيراتيجية تعلم اللغة العرابية نمودج اكسفورد في المدرسة الإبتدائية - Vindayani, Fika (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2020)
One of the elements of learning Arabic is the student's Arabic learning strategy. But there are still some students who have not found the right strategy for learning Arabic, because of a lack of knowledge about Arabic learning strategies, especially the Oxford model of language learning strategies. The purpose of this study was to describe the implementation of the Arabic language learning strategy for students in the Oxford model of Madrasah Ibitidaiyah Al Islam Kartasura students. This research is descriptive qualitative, as for the research site at Madrasah Ibitidaiyah Al Islam Kartasura. This research was conducted from March to June 2020. The subjects in this study were students of class V A at Madrasah Ibitidaiyah Al Islam Kartasura. The informants in this study were the fifth-grade Arabic teachers at Madrasah Ibitidaiyah Al Islam Kartasura. Data collection methods used were interviews, observation, and documentation. The conclusion of this study is that students use Arabic learning strategies in the Oxford model because there are indications that students are using their learning. The strategies used are memory strategies, cognitive strategies, compensation strategies, metacognitive strategies, affective strategies, and social strategies. The strategy that is often used by students is the memorial strategy.